Alterations in egg white-related genes expression in response to hormonal stimulation. Issue 5 (November 2020) - Lee, Minkyeong; Yang, Changwon; Song, Gwonhwa; Lim, Whasun
Abstract : The reproductive tract in avian females is sensitive to hormonal regulation. Exogenous estrogen induces immature oviduct development to improve egg production after molting. In this process, regressed female reproductive tract is regenerated in response to the secretion of estrogen. However, there is limited knowledge on the physiological mechanisms underlying the regulation of the avian female reproductive system. In our previous study, results from microarray analysis revealed that the expression of genes encoding egg white proteins is affected during molting. Herein, we artificially induced the molting period in chickens through a zinc-containing diet. Subsequently, changes in the expression of genes encoding egg white proteins were confirmed in the oviduct tissue. The levels of MUC5B, ORM1, RTBDN, and TENP mRNA were significantly high in the oviduct, and the genes were repressed in the regression phase, whereas these were expressed in the recrudescence phase, particularly in the luminal epithelium and glandular epithelium of the oviduct, during molting. Moreover, we observed that gene expression was induced in the magnum, the site for the secretion of egg white components. Next, differences in expression levels of the four genes in normal and cancerous ovaries were compared. Collectively, results suggest that the four selected genes are expressed in the female chicken reproductive tract in response to hormonal regulation, and egg white protein-encoding genes may serve as modulators of the reproductive system in hens.